Ranking Fluctuating Asymmetry in a Dot Figure and the Significant Impact of Imagining a Face. (March 2013) - Neby, Magne; Folstad, Ivar
Fluctuating asymmetry and averageness is correlated with our perception of beauty in human faces. Yet, whether deviations of centrality in the positioning of the eyes, the nose, and the mouth have different effects on our perception of asymmetry in a holistic human face, is still uncertain. In this study we aimed to test the relative effect of decentralising the horizontal position of three sets of paired dots representing eyes, nostrils, or mouth from the vertical midline of ambiguous dot figures, vaguely resembling a face. The figures were ranked according to perceived asymmetry by human observers. When associating the figures with non-facial objects (eg a butterfly), none of the figures' rank distribution differed from each other. However, when observers imagined the figures to represent a human face, the figure with the decentralised pair of dots representing the nostrils was significantly ranked as more asymmetric than the other figures. This result provides indications that the brain may deal with information about facial asymmetry and averageness heavily depending on the centrality of the nasal region.